What is an Effective Self Help Guide? Literature Review and Meta Analysis - Riskiyana Prihatiningsih; Indriyana Rachmawati; Diniy Hidayatur Rahman (Department of Guidance and Counseling, FIP, Undiksha, 2021)
Self-help has become an interesting issue lately and is an alternative intervention that is of interest to individuals to help mental health problems experienced. Various models of self-help guides are available and can be accessed by individuals, including through the internet and social media. The purpose of this study was to determine the effective form of self-help for individuals who experience mental health problems. The research method used is literature review and as many as 8 of the 86 articles reviewed during the last two years. The articles that have been obtained were analyzed and synthesized using content analysis techniques to obtain an overview of self-help guidelines. The results showed that self-help guides were effective for individuals, including training materials, intervention practices, and manuals for helpers or therapists who support counselees to practice the guidelines.